A potential environmental sustainability of wood ash in normal and geopolymer concrete – A Review - Muhammad Nura, Isa; Hanizam, Awang; Khairunisa, Muthusamy (Politechnika lubelska, 2023)
The production of cement for concrete has led to the emission of carbon dioxide (CO₂) into the atmosphere, which has contributed to global warming. Moreover, the excessive amount of industrial waste from biomass energy production landfilled in our environments is continuously causing sustainability challenges. However, several studies were carried out to ascertain the possibilities of using these waste materials in concrete production to address the cement and waste disposal sustainable issues simultaneously. The present study reviewed multiple studies carried out on wood ash (WA) application in both normal and geopolymer concrete with an emphasis on fresh, hardened, and durability properties. WA can be used to replace cement in conventional mortar/concrete at up to 20% replacement level, similarly, it was revealed that WA can be effectively utilized to replace ground granulated blast furnace slag (GGBS) or pulverized fly ash (PFA) at up to 50% replacement level in geopolymer mortar/concrete production. The sustainability impacts of WA utilization in concrete production were presented and discussed. Results of these findings revealed its suitability as supplementary cementitious material, but still there exists a gap in its utilization in geopolymer concrete.